The value of imbibition and syneresis for dental impression on red seaweed: a laboratory experiment - Indahyani, Didin Erma; Barid, Izzata; Anggraeni, Priska Amelia (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Alginate is a type of elastic dental impression, which is an irreversible hydrocolloid. The main components in sodium alginate can be obtained naturally through the extraction process from seaweed (Kappaphycus alvarezii). Several physical characteristics must be fulfilled by dental impressions, such as dimensional stability related to imbibition and syneresis. ANSI/ADA specification No.18 regarding the maximum permitted change in alginate impression materials may not exceed 0.5%. This research aimed to analyze the value of imbibition and syneresis on dental impressions of red seaweed extract (K.alvarezii). Methods: The research was conducted using an experimental laboratory method with a post-test-only control group design. There were two groups, namely the control group of commercial dental impressions and the treatment group using dental impressions with the sodium alginate extracted from red seaweed (K.Alvarezii) by the acid method, and the FTIR test was performed to analyze compound sodium alginate. Imbibition and syneresis measurements were carried out using a calliper on a plaster cast model from negative mould casting results, where previously, the mould was soaked in water for imbibition and evaporated for syneresis. Results: Imbibition and syneresis tests showed that the impression material group with sodium alginate from red algae was significantly lower than those with commercial impression materials. It was concluded that the impression material with sodium alginate from red seaweed had an effect on reducing the percentage of syneresis (p≤0.05) and imbibition (p≤0.05) of the impression material. Based on the results of our research, it was found that the alginate impression material extracted from red seaweed (k.alvarezii) had an imbibition value of 0.33% (p≤0.05) and syneresis of 0.28%, (p≤0.05) lower compared to alginate impression materials. commercial alginate impression material. Conclusion: The imbibition and syneresis values of red seaweed alginate show an excessively low value compared to commercial alginates. KEYWORDS dental impression,sodium alginate, Kappaphycus alvarezii, imbibition, syneresis